Physico-chemical attributes of water of Hakaluki Haor, Sylhet, Bangladesh (Jahangirnagar University Journal of Biological Sciences, 2016)
Water quality assessment has been carried out in the Hakaluki Haor of greater Sylhet district during May, 2013 to February, 2014. Water samples were collected from 5 spots during 4 seasons and a total of 15 physico-chemical parameters were studied. Significant seasonal variation was observed in all seasons among physico-chemical parameters. pH values varied from 5.9 - 7.1, water temperature varied from 23.7 26.7OC, transference varied from 23-53 cm, TSS varied from 18.1-192 mg/l, TDS varied 25-193.5 mg/l, EC varied from 30-680 ?s/cm , DO content of water varied from 4.6 - 5.6mg/l, BOD varied from 0.2-2.614 mg/l, COD varied from 38-312 mg/l, NO3-N varied from 0.1-30.4 mg/l, NH3 varied from 0.9-2.18 mg/l, alkalinity varied from 12-42 mg/l and PO4 varied from 0.9 -13.4 (mg/l). Agricultural and inorganic pollutants have been observed as the main causes of the Haor water pollution.Jahangirnagar University J. Biol. Sci. 3(2): 67-72, 2014 (December)